About the biology of Steraspis fastuosa Gerstaecker in Atacora region, northern Benin (Coleoptera, Buprestidae) - Vayssières, Jean-François; Bellamy, C.L.; Goergen, Georg E.; Adandonon, A.; Sinzogan, A.A.C.; Curletti, G. (2013)
Although numerous adults of the buprestid genus Steraspis Dejean, 1833, have been captured in West Africa, little is known about the biology of the known species, especially about their immature stages. The objective of the present field observations was to increase the knowledge on the biology of a common but localized species in Benin. In early 2012, a field survey was conducted to search for the immature stages of Steraspisspecies, especially S. fastuosa Gerstaecker, 1871. In May 2012, a nymph of S. fastuosawas found within the taproot of Acacia hockiiDe Wild (Fabaceae) and also an adult of the same species within the taproot of a nearby A. hockii. This well-developed adult was found at 7 cm below the soil surface and ready to emerge from the taproot. Prior to pupation, the mature larva had cut along the collar of the taproot, thus facilitating the emergence of the adult. This is the first report on the developmental biology of this species in West Africa.